Media and communication ethics: legal perspectives and the public expectations - Mohamed, Duryana; Mohd Badrol Afandi, Nor Hafizah (Lexis Nexis, 2019)
Media plays a very important role in the development of society. The society develops and become a modernised society through many ways. One of them is through development in media and communica-tion. The media is expected to deliver correct information, protect public interests and create public awareness. In the internet environment, news posted through online media can reach readers almost instantly and will quickly become viral. But, sometimes the news contains false information. When the public receives fake news, they blame the media and the latter has to ensure they comply with relevant laws and Code of Practice for reporters. However, in order to avoid any issues arising, people in the media industry such as the journalists, reporters, publishers and Internet Service Providers (ISP) are recommended to understand media and communication ethics, their rights and duties under the laws and the possible challenges ahead. This paper discusses those issues by giving special reference to defamation cases online and offline involving media related people and the industries.